Using internet of things (IoT) to knowledge management to improve organizational performances: A case study on selected companies from different industries in the Philippines - Ancla, Lawrence Xavier C. (Animo Repository, 2023)
From the rise of the Web 3.0 age, a relatively new and unexplored technology called the Internet of Things (IoT) has entered. This technology allows different devices to share data and information in real-time through the internet, which can be useful in the business sector. The purpose of this study is to focus on how IoTs are capable to share data and information in real time, and see their effect on improving knowledge management in organizations, specifically in their performance in their internal processes. This study utilized a qualitative embedded cross-case study investigating the existing IoT capabilities of 5 companies in different industries in the Philippines, how the IoTs affect their Knowledge Management processes, and how the affected knowledge improves organizational internal process performance. To collect the data, the study conducted interviews, focus group discussions and surveys with the selected companies. The results of this research show that IoT technology improves the knowledge management processes with its ability in producing, storing, sharing and using knowledge. With the affected knowledge processes, companies who use these IoTs benefit in their internal processes as it allows them to be more efficient in their operations and improving their products and services. This study provides tangible recommendations in maximizing IoTs in their organization that can be adopted and replicated by other enterprises.